Design and Implementation of Multifunction Relay Based on Microcontroller - Ali Abdulsattar Hameed; Ahmed Jasim Sultan; Mehdi F. Booneya (Journal of Techniques)
The power systems are exposed to many abnormal conditions, so an advanced protection system must be provided to stand up to these challenges. Protection devices evolved continuously with the development of power systems. The accuracy, high response, reliability, and speed of fault detection are required in the operating mode of multi-function protective relays. A Multifunction Relay has been designed and implemented, which consists of three types of relays: over current relay OCR, over/under voltage relay OVR/UVR, and differential relay DFR. The relays OCR, OVR/UVR, and DFR are designed according to the standards IEC 60255, IEEE 1159, and IEEE C37.91, respectively, based on Arduino MEGA. The multi-function relay was implemented to work on a single phase.